Importance-performance analysis as a tool to guide employer branding strategies in the IT-BPM industry. Issue 1 (21st February 2019) - Deepa, R.; Baral, Rupashree
Abstract : Purpose: Based on attribute research in marketing, importance-performance analysis (IPA) provides a useful analogy to examine employer branding concepts. The purpose of this paper is to use IPA to evaluate employees' perceptions of important employer value proposition (EVP) attributes and their corresponding psychological contract fulfillment scores. IPA is applied to 40 EVP attributes and their corresponding EVP dimensions – "Economic Value", "Development Value", "Social Value", "Work Value" and "Employer Reputation." Further, the paper examines the difference between highly engaged and less engaged employees in their relationship to importance and fulfillment of the five EVP dimensions. Design/methodology/approach: Data were drawn from information technology-business process management employees ( n =520) in India through a questionnaire survey. The IPA matrix was used to plot the importance and fulfillment scores. Independent samples t -test was used to assess the difference between high and low engagement scores. Findings: The results indicate that several EVP attributes fall within the "Concentrate Here" quadrant that requires more focus. With respect to EVP dimensions, social value needs focus; economic value received "Low Priority"; and work value and employer reputation are identified as "Potential Overkill." The findings also suggest that, organizations should engage employees across all dimensions, by both prioritizing and fulfilling their obligations promptly. Practical implications: The study highlights the need for HR practitioners and academicians to draw insights from attribute research in marketing to effectively devise the employer branding strategy of individual organizations. Originality/value: This paper is the first of its kind to apply IPA to EVP attributes, which contributes to the growing literature on employer branding.